The Use of Interactive Media to Improve Students' Conceptual Understanding in Islamic Education Learning at SD Negeri 0301 Sosopan - Harahap, Yuni Nazifa; Siregar, Seri Bulan (Journal of Indonesian Primary School, 2024)
This study aims to analyze the effectiveness of the use of interactive media in improving elementary school students' understanding of Islamic Religious Education subjects. The research method used is a quasi-experimental with a pretest-posttest control group design. The research sample consisted of two groups of fifth grade elementary school students, namely the experimental group using interactive media and the control group using conventional methods. The research instruments were in the form of comprehension tests before and after treatment and student response questionnaires regarding the use of interactive media. The results of the study showed that there was a significant increase in the understanding of students using interactive media compared to the control group. This is evidenced by the difference in the average posttest score between the two groups, where the experimental group scored higher. In addition, students gave a positive response to the use of interactive media because it was more interesting, easier to understand, and increased learning motivation. Thus, it can be concluded that the use of interactive media is an effective strategy in learning Islamic Education in elementary schools. The results of this study are expected to be a reference for educators in developing more innovative learning methods.